Optical characteristics of short fiber-reinforced composite in bilayered structure - Sarmiala, Arvi (My University, 2022)
Purpose: The aim of this in vitro study was to optically evaluate required thickness of particulate filled composite (PFC) used on top of short fiber-reinforced composite (SFRC) in direct bilayered composite structure. Materials and Methods: Three groups of SFRC materials were studied: everX Flow Dentin (eXD), everX Flow Bulk (eXB) and everX Posterior (eXP) (all materials from GC, Tokyo, Japan). Samples were made in 4 mm deep cavities in transparent molds with a SFRC substructure and a PFC veneer (GC G-ænial Universal Injectable A3) on top. Six different SFRC-PFC ratio combinations were tested with each SFRC material to find out the required PFC thickness where the human eye cannot detect the underlying SFRC material compared to PFC reference cylinder. The used PFC thicknesses were 2.0, 1.5, 1.2, 1.0, 0.7 and 0.5 mm. Test samples (n=5 /thickness /material) were made in two steps and colours were optically measured with a spectrophotometer (CM-700d, Konica-Minolta, Tokyo, Japan). Results: In all SFRC materials color change values (ΔE) acted almost inversely proportionally to PFC thickness (R2 > 0.85). All three tested SFRC materials had a statistically significant difference in ΔE-values, when veneering PFC thickness was 1.0 mm (p< 0.05). In the groups where PFC material thickness was 2.0 mm, the flowable SFRCs (eXD and eXB) showed statistically significant difference compared to packable SFRC (eXP) (p< 0.05). Conclusion: The thickness of veneering PFC affects the optical properties of bilayered restorations. The thickness of PFC should be taken into consideration, when using bilayered SFRC structures in highly aesthetic areas.
Keywords: Optical characteristics, short fiber reinforced composite, biomimetic composite restoration, bilayered composite restoration, color change